New framework for recombination and adaptive evolution analysis with application to the novel coronavirus SARS-CoV-2. Issue 5 (22nd April 2021) - Wang, Yinghan; Zeng, Jinfeng; Zhang, Chi; Chen, Cai; Qiu, Zekai; Pang, Jiali; Xu, Yutian; Dong, Zhiqi; Song, Yanxin; Liu, Weiying; Dong, Peipei; Sun, Litao; et al.
Abstract: The 2019 novel coronavirus (SARS-CoV-2) has spread rapidly worldwide and was declared a pandemic by the WHO in March 2020. The evolution of SARS-CoV-2, either in its natural reservoir or in the human population, is still unclear, but this knowledge is essential for effective prevention and control. We propose a new framework to systematically identify recombination events, excluding those due to noise and convergent evolution. We found that several recombination events occurred for SARS-CoV-2 before its transfer to humans, including a more recent recombination event in the receptor-binding domain. We also constructed a probabilistic mutation network to explore the diversity and evolution of SARS-CoV-2 after human infection. Clustering results show that the novel coronavirus has diverged into several clusters that cocirculate over time in various regions and that several mutations across the genome are fixed during transmission throughout the human population, including D614G in the S gene and two accompanied mutations in ORF1ab. Together, these findings suggest that SARS-CoV-2 experienced a complicated evolution process in the natural environment and point to its continuous adaptation to humans. The new framework proposed in this study can help our understanding of and response to other emerging pathogens.